Different Strategies of Stabilization of Vanadium Oxidation States in Lagao3 Nanocrystals - Kniec, Karolina; Marciniak, Lukasz (Frontiers in Chemistry, 2019)
The spectroscopic properties of LaGaO3, doped with V ions, were examined in terms of the possibility of the stabilization of particular vanadium oxidation states. It was shown that three different approaches may be applied in order to control the ionic charge of vanadium, namely, charge compensation, via incorporation of Mg2+/Ca2+ ions, citric acid (CA)-assisted synthesis, with various CA concentrations and grain size tuning through annealing temperature regulation. Each of utilized method enables the significant reduction of V5+ emission band at 520 nm associated with the V4+→O2- CT transition in respect to the 2E→2T2 emission band of V4+ at 645 nm and 1E2→3T1g emission band of V3+ at 712 nm. The most efficient V oxidation state stabilization was obtained by the use of grain size modulation, which bases on fact of different localization of the V ions of given charge in the nanoparticles. Moreover the CA-assisted synthesis of LaGaO3:V determines V valence states but also provides significant separation of the nanograins. It was found that superior charge compensation was achieved when Mg2+ ions were introduced in the matrix, due the more efficient lability, resulting from the comparable ionic radii between Mg2+ and V ions.